Yeast Diversity in Thai Traditional Fermentation Starter (Loog-pang) - Savitree Limtong; Somporn Sintara; Poonpilai Suwanarit; Napha Lotong (Agriculture and Natural Resources, 2002)
From 38 samples of loog-pang-kao-mag, 31 of them contained yeasts in the range of 3.9×104 – 2.9×107 cfu/g while 7 samples did not. In 19 samples of loog-pang-lao yeast numbers were 2.9×104 – 5.0×107 cfu/g. Forty-three isolates of yeast were obtained from all samples of loog-pang-kao-mag and 49 were obtained from loog-pang-lao. Among them, 31 isolates from loog-pang-kao-mag and 20 isolates from loog-pang-lao were identified as Saccharomycopsis fibuligera. The other yeast species presented in both types of loog-pang were Pichia anomala (8), Issatchenkia orientalis (6), P. burtonii (6), P. fabianii (4), Candida rhagii (4), C. glabrata (3), Torulaspora globosa (3), P. mexicana (2) and 1 isolate each of P. heimii, Rhodotorula philyla, Saccharomyces cerevisiae, T. delbrueckii and Trichosporon asahii. S. fibuligera was the single yeast species found in 22 samples (70.97%) of loog-pang-kao-mag and 7 samples (36.84%) of loog-pang-lao. In addition, 7 samples (22.58%) of loog-pang-kao-mag consisted of S. fibuligera together with 1-2 species of other yeast, while 9 samples (47.37%) of loog-pang-lao consisted of S. fibuligera and 1-4 other yeast species. Forty-six from 47 isolates of S. fibuligera revealed strong amylolytic activity, express as ratio of clear zone diameter and colony diameter on soluble starch agar, in the range of 1.93-3.25. However, most of them produced low ethyl alcohol, i.e., less than 2 %v/v from 18 % glucose at 48 hours. On the contrary, other yeast species showed low amylolytic activity but high or moderately high in alcohol fermenting ability. Among the isolates that fermented high alcohol contents were T. globosa YKM032 (6.03%v/v), I. orientalis YMK036 (6.01%v/v), P. burtonii YKM034 (6.00%v/v) and P. burtonii YL048 (5.99%v/v). The only one isolate of S. cerevisiae produced relatively low ethyl alcohol at 4.68%v/v.